Postoperative Care in Aesthetic Rhinoplasty Patients - Apaydin, Fazil; Stanic, Lara; Unadkat, Samit; Saleh, Hesham A. (Facial Plastic Surgery, 2018)
After rhinoplasty, during the first 24 hours, the patients should be closely monitored for pain and discomfort, nausea and vomiting, and cool compresses must be applied regularly to decrease edema and ecchymosis. In the early postoperative period of the first month, the sutures, cast, and splints are usually removed during the first week. Then the patient is followed-up at 1, 3, 6, and 12-month intervals routinely to observe healing. In the meantime, any kind of intranasal and extranasal complications should be noted. The outcome measures such as ROE, NOSE, or SCHNOS should be used 3 to 6 months after surgery. If the patient is closely followed-up, then any unwanted complication or dissatisfaction can be solved after 6 to 12 months.
Keywords: rhinoplasty; preemptive analgesia; postoperative pain and discomfort; nausea; vomiting; steroid use; absorbable sutures; taping; arnica